Unraveling the Sweet Secrets of HCC: Glucometabolic Rewiring in Hepatocellular Carcinoma - Sheraz Ahmad Bhat PhD; Zeenat Farooq PhD; Hagar Ismail BS; Irene Corona-Avila BS; Md. Wasim Khan PhD (Technology in Cancer Research & Treatment, 2023)
Hepatocellular carcinoma (HCC) is the primary form of liver cancer. It causes ∼ 800 000 deaths per year, which is expected to increase due to increasing rates of obesity and metabolic dysfunction associated steatotic liver disease (MASLD). Current therapies include immune checkpoint inhibitors, tyrosine kinase inhibitors, and monoclonal antibodies, but these therapies are not satisfactorily effective and often come with multiple side effects and recurrences. Metabolic reprogramming plays a significant role in HCC progression and is often conserved between tumor types. Thus, targeting rewired metabolic pathways could provide an attractive option for targeting tumor cells alone or in conjunction with existing treatments. Therefore, there is an urgent need to identify novel targets involved in cancer-mediated metabolic reprogramming in HCC. In this review, we provide an overview of molecular rewiring and metabolic reprogramming of glucose metabolism in HCC to understand better the concepts that might widen the therapeutic window against this deadly cancer.